The 'Old Arctics': notices of Franklin Search expedition veterans in the British press, 1876–1934. (6th October 2015) - McCorristine, Shane; Herrmann, Victoria
ABSTRACT: The lives of the commanders and officers associated with the British naval searches for the lost John Franklin northwest passage expedition in the 1850s are well-known through their own writings or those of later biographers. The post-Arctic careers of ordinary crew members, on the other hand, are barely known at all. Following digital searches of nineteenth and early-twentieth century British newspapers, we have compiled a list of some notices, obituaries, and reminiscences that shed light on the later years of the 'Old Arctics'.